Revenue Management Pricing in Douro Hotels - Correia, Elisete (2016)
The Douro Palace Hotel management wants to develop a software that helps them with the dynamic pricing of the hotel rooms. Revenue Management software is widely used for data analysis of demand and prices. However the hotel barely follows the software recommendations for pricing decisions, mainly due to the lack of understanding of the rationale and the inherent diffi culty in validating pricing decisions. The hotel would like to have a reliable model in order to give to the manager an overview of the business and how to act to improve the sales.In this report, we present two distinct methodologies to address the hotel request. The fi rst approach is excel based and more practically oriented towards to be an immediate help of the current pricing decisions. A second approach is more formal, mathematically speaking, but requires a more time consuming implementation. It is based on a recent operations management/ operations research paper.